2015
DOI: 10.1155/2015/626835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxic, Cytotoxic, Mutagenic, and Antimutagenic Activities of Natural and Technical Cashew Nut Shell Liquids Using theAllium cepaandArtemia salinaBioassays

Abstract: The cashew nut releases a substance that is known as cashew nut shell liquid (CNSL). There are both natural (iCNSL) and technical (tCNSL) cashew nut shell liquids. This study used an Artemia salina bioassay to evaluate the toxic effects of iCNSL and tCNSL cashew nut shell liquids. It also evaluated the toxicity, cytotoxicity, and mutagenicity of CNSL and its effects on the damage induced by copper sulfate (CuSO4·5H2O) on the meristems' root of Allium cepa. Effects of the damage induced by CuSO4·5H2O were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…The phytochemical screening of the extract revealed the presence of coumarins, flavonoids, tannins, and triterpenes ( Table 1 ). Toxicity of the extract was firstly evaluated using the microcrustacean A. salina , which is often used as a preliminary indicator of general toxicity of plant compounds; also, it is reported that toxicity to A. salina has a correlation with possible antitumor activity [ 30 , 31 ]. The results showed that the extract had no toxicity at all the tested concentrations, suggesting that it does not have a general toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical screening of the extract revealed the presence of coumarins, flavonoids, tannins, and triterpenes ( Table 1 ). Toxicity of the extract was firstly evaluated using the microcrustacean A. salina , which is often used as a preliminary indicator of general toxicity of plant compounds; also, it is reported that toxicity to A. salina has a correlation with possible antitumor activity [ 30 , 31 ]. The results showed that the extract had no toxicity at all the tested concentrations, suggesting that it does not have a general toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…If these lines of defense are still insufficient, the body may also facilitate the excretion of xenobiotics through detoxification enzymes, making them more water soluble and, thus, assisting their elimination by the kidneys ( Cordon-Cardo et al , 1989 ; Hooiveld et al , 2001 ), while modulating the DNA repair system. This last line of defense is associated with bioantimutagenesis, in which enzymes are modulated by test compounds, thus favoring the correction and integrity of the genetic material, reducing the probability of developing cancer ( Oliveira et al , 2009b ; Nakamura et al , 1999 ; Di Giacomo et al , 2014 ; Leite et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were used: interface = 270°C, injector = 250°C, initial temperature = 60°C (2 min), 4.0 mL/min to 180°C (4 min), and 10 mL/min to 260°C (10 min). Identification was achieved by comparing mass spectra (43 to 4500 Da, electron impact ionization, 70 eV) MS [16,25].…”
Section: Cnsl Methylation Reaction and Gc-ms Analysismentioning
confidence: 99%